Kate Knapp: capstone - Knapp, Kate, artist (Colorado State University. Libraries, 2016)
The artist's statement: Whenever I begin a project I always ask myself to pick three to five adjectives that foreshadow the look and feel I'm going for. So when describing my work as a whole, I have to start the same. My work is thoughtful, simple, and clean. I love working with negative space, as it's as power as the imagery and typography. I try to find the balance between giving you, the viewer, a strong visual to look at, with a balance of white space so your eyes can wonder. I have a strong use of vectors and my own photography in my work. What can I say, I'm a 90's kid so I love the vector style and I've been working to develop my own style within the vector parameters. Photography is another passion of mine, so I love to incorporate it into my designs whenever possible.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design